Handbook of labor economics (Elsevier North Holland, 1999)
The subject matter of labor economics continues to have at its core an attempt to systematically find empirical analyses that are consistent with a systematic and parsimonious theoretical understanding of the diverse phenomenon that make up the labor market. As before, many of these analyses are provocative and controversial because they are so directly relevant to both public policy and private decision making. In many ways the modern development in the field of labor economics continues to set the standards for the best work in applied economics. This volume of the Handbook has a notable representation of authors - and topics of importance - from throughout the world